First record of Amblyomma rotundatum Koch, 1844 (Acari: Ixodidae) parasitizing Paleosuchus palpebrosus Cuvier, 1807 (Reptilia:Crocodylidae), in the western border of Pantanal, Mato Grosso do Sul, Brazil - Morais, Drausio H. [UNESP]; Strüssmann, Christine; de Carvalho, Vinícius T.; Kawashita-Ribeiro, Ricardo A. (My University, 2010)
This is the first record of Amblyomma rotundatum parasitizing Paleosuchus palpebrosus. This record was made during a herpetofaunal study carried out in high elevation habitats that are under protection in the mountain range Serra do Amolar, located in the western border of Brazilian Pantanal, in the state of Mato Grosso do Sul.
Keywords: Amblyomma rotundatum; Brazil; Paleosuchus palpebrosus; Pantanal; Parasitism